First step optimization of glucose oxidase production by indigenous fungal strain / \c Nurul Ain Borhan - Nurul Ain Borhan (School of Bioprocess Engineering, University Malaysia Perlis, 2011)
Glucose oxidase (D-glucose:oxygen 1-oxidoreductase; EC 1.1.2.3.4) catalyzes the oxidation of D-glucose to gluconic acid, by utilizing molecular oxygen as an electron acceptor with simultaneous production of hydrogen peroxide. A number of nutritional factors influencing glucose oxidase (EC 1.1.3.4) production by indigenous fungal strain were studied. The synthesis of glucose oxidase by indigenous fungal strain was investigated by using submerged fermentation at 30 2oC and 200 rpm for 110 hours. Primarily, nutritional component were selected by significance of each component with respect to glucose oxidase production was identified by Plackett-Burman design (eight variables including seven nutritional, e.g sodium nitrate (NaNO3), potassium phosphate (KH2PO4), magnesium hydrate sulfate (MgSO4.7H2O), iron hydrate sulfate (FeSO4.7H20), peptone, calcium carbonate (CaCO3), glucose and one dummy or unassigned variable were studied with twelve experiment). The outcome of Plackett-Burman design showed four factors that affected the glucose oxidase production, which are glucose, peptone, NaNO3 and CaCO3.